Harsh Parenting and Food Insecurity in Adolescence: The Association with Emerging Adult Obesity - Gillette, Meghan T. (Journal of adolescent health, 2016)
In the U.S., as of 2012, more than one in three youth were overweight or obese [1]. This is a critical health issue, as being overweight or obese (OW/OB) during adolescence increases the risk of adulthood diseases, including but not limited to cardiovascular and heart disease, diabetes, stroke, cancer, and osteoarthritis [2]. Understanding the pathways to obesity is critical for implementation of successful prevention and intervention programs. One of the pathways leading to OW/OB is through social and economic experiences within the family